Harnessing multisector data to guide policy decision-making to help reduce malnutrition: findings from implementing the National Information Platforms for Nutrition in Africa, Asia and South America - Carmel M Dolan; J Shojam; P Geniez; B Baille; L Barrington; E Onsomu; I Kiplagat; J Katungu; S Kipruto; M Balarabe (Journal of Global Health Economics and Policy)
# Background An independent assessment was undertaken of the National Information Platform for Nutrition (NIPN) initiative. It examined whether NIPN has contributed to supporting the capacities of national authorities in Scaling up Nutrition (SUN) Movement countries to harness multisector nutrition-relevant data for informing nutrition policy and decision-making.